Heparin-Neutralizing Activity, Total Progressive Antithrombin and the Ethanol Gel Test in Acute Chest Pain - Raper, C G L; Love, H (Thrombosis and Haemostasis, 1978)
92 patients admitted to a cardiac monitoring unit with chest pain were investigated. The mean heparin-neutralizing activity of the 34 patients with severe myocardial infarction was found to be significantly different from the mean of 70 normal controls. However, there was considerable overlap between individual observations and the normal range. Only 5 of the 34 patients with severe myocardial infarction had antithrombin levels outside the normal range. In patients with a severe myocardial infarct tested on the 2nd and 3rd day after infarction there was a significant increase in the number of positive ethanol gel tests compared with the other patients studied.